Unraveling Cyberlaw and Information Sharing Trends: A Comprehensive Analysis - Taufany, Firdaus Enov At; Purwaningsih, Sri Budi; Pristiwanto (Proceedings of The ICECRS, 2023)
This data article presents a comprehensive analysis of the evolving landscape of Cyberlaw and Information Sharing, extracted from Lens.org using the search terms Cyberlaw OR Cyber Law AND Information Sharing, specifically focusing on law journals and journal articles. The study identifies key trends across various parameters such as top institutions (e.g., the University of Sydney), scholarly works over time (peaking in 2015), and the most active fields of study (primarily in law). It also highlights active contributors like authors Nafiseh Ghafournia and Patricia L., indicating a prolific output. The scatter plot analysis reveals a concentration of 55 significant academic works. Regionally, active participation emanates notably from the American continent. The leading publisher, MDPI AG, emerges as a key player in disseminating research in this domain. The study's outcomes provide valuable insights into the current academic landscape, offering a wealth of information for scholars and institutions interested in the dynamic intersection of Cyberlaw and Information Sharing. Highlights : Comprehensive analysis of Cyberlaw and Information Sharing trends based on Lens.org data. Identified top institution: the University of Sydney, and prolific authors Nafiseh Ghafournia and Patricia Peak scholarly works observed in 2015, showcasing the evolving landscape of law-related research. Keywords: Cyberlaw, Information Sharing, Academic Trends, Top Contributors, Global Perspectives